1987
DOI: 10.1037/0022-3514.52.1.59
|View full text |Cite
|
Sign up to set email alerts
|

Selecting representative trait adjectives.

Abstract: A strong argument has been made for specifying the possible characteristics of personality by using trait adjectives from the natural language. This argument implies a rationale for the selection of variables to measure personality characteristics: One should select variables to be representative of trait adjectives in the natural language. In this study I argue that this rationale has never been carried through, and I make an attempt to do so. This requires defining a pool of trait adjectives, classifying th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
134
0
6

Year Published

1988
1988
2011
2011

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 183 publications
(145 citation statements)
references
References 14 publications
5
134
0
6
Order By: Relevance
“…Cloninger (1988), Gough (1987), andTellegen (1982) also have three-factor theories. Peabody (1987) noted that N-related trait terms are relatively rare in English, and thus that the inclusion of a separate emotional stability factor is not justified by analyses of trait adjectives. Digman (1985) suggested that there might be two higher order factors: Socialization (combining A and C with low N) and Self-Actualization (combining E, O, and low N); and Hogan (in press) stated that "these five factors can be reduced to three through higher order factor analysis.…”
Section: Objections and Responsesmentioning
confidence: 99%
“…Cloninger (1988), Gough (1987), andTellegen (1982) also have three-factor theories. Peabody (1987) noted that N-related trait terms are relatively rare in English, and thus that the inclusion of a separate emotional stability factor is not justified by analyses of trait adjectives. Digman (1985) suggested that there might be two higher order factors: Socialization (combining A and C with low N) and Self-Actualization (combining E, O, and low N); and Hogan (in press) stated that "these five factors can be reduced to three through higher order factor analysis.…”
Section: Objections and Responsesmentioning
confidence: 99%
“…If the goal of the lexical approach to personality is to build a taxonomy of the major underlying personality dimensions, examining the words we use in everyday life to describe ourselves may be a good place to start to build a taxonomy of the major dimensions along which people think about themselves (Peabody, 1987;Tellegen, 1993). By sampling from the most frequently used adjectives in self-descriptions, we build on the capabilities of several automated language tools and principle components analysis to extract major themes in openended self-descriptions.…”
Section: Descibing People By the Ways They Think: The Meaning Extractmentioning
confidence: 99%
“…Peabody and Goldberg used a set of variables selected with the goal of achieving an adequate representation of common English trait adjectives (Peabody, 1987). A comparison of their selection with that of Cattell showed that Cattell's 35 variables included markers for all the domains included by Peabody and Goldberg but did so in an unrepresentative manner.…”
Section: Five Broad Dimensions Of Personality Descriptionmentioning
confidence: 99%